RegTech—the application of modern information technology in regulatory affairs: areas of interest in research and practice - Michael Becker; Kevin Merz; Rüdiger Buchkremer (Intelligent Systems in Accounting, Finance and Management, 2020)
We provide a high-level view on topics addressed in scientific articles about regulatory technology (RegTech), with a particular focus on technologies used. For this purpose, we first explore different denominations for RegTech and derive search queries to search relevant literature portals. From the hits of that information retrieval process, we select 55 articles outlining the application of information technology in regulatory affairs with an emphasis on the financial sector. In comparison, we examine the technological scope of 347 RegTech companies and compare our findings with the scientific literature. Our research reveals that `compliance management' is the most relevant topic in practice, and `risk management' is the primary subject in research. The most significant technologies as of today are `artificial intelligence' and distributed ledger technologies such as `blockchain'.
Keywords: 650; artificial intelligence; compliance management; distributed ledger technologies; regulatory technology; risk management